Geometric Sequences - Explicit & Recursive
Explicit & Recursive - How it Works - Video
Example 1
Example 1:
For this example we have to use the formula, an = a1 * rn-1. The n is the number of term that we want. In this case the example wants the 1st term, the 2nd term, the 3rd term, and the 10th term.
The 1st term
=> 3 *(-1/4)1-1
=> 3 *(-1/4)0
=> 3 * 1
=> 3
The 2nd term
=> 3 *(-1/4)2-1
=> 3 *(-1/4)1
=> 3 * (-1/4)
=> (-3/4)
The 3rd term
=> 3 *(-1/4)3-1
=> 3 *(-1/4)2
=> 3 * (1/16)
=> 3/16
The 10th term
=> 3 *(-1/4)10-1
=> 3 *(-1/4)9
=> 3 * (-1/262,144)
=> -3/262,144
Example 2
Example 2:
For this example we have to use the formula, an = a1 * rn-1. This time we have to find first term and the ratio so that we can create the formula to find any term. We have been given the 3rd term and the 6th term. Our first step is to find the ratio. Once we found the ratio, we can find our 1st term. Once we have the 1st term and the ratio we can create the formula to find any term.
1st Term
=> -6 = a1 * r2
=> -6 = a1 * (-2)2
=> -6 = a1 * 4
=> -6/4 = a1
=> -3/2 = a1
=> Write a1 equation
=> Substitute -2 for the ratio
=> Square -2
=> Divide by 4
=> Simplify
Example 3
Example 3:
For
Example 4
Example 4:
For